Conductivity-viscosity-structure: unpicking the relationship in an ionic liquid. - Salanne, M; Simon, C; Turq, P; Madden, P (2007)
The relationships between the ionic mobility, the viscosity, and the atomic-scale structure are investigated in computer simulations of mixtures of LiF and the network glass-forming material BeF(2). The simulations span a wide range of compositions, across which the fluidity of the system changes greatly due to the break-up of the Be-F network by the addition of the LiF. The relationship between the conductivity and viscosity passes from that expected for independently diffusing ions in the dilute mixtures to strongly decoupled Li+ migration through a viscous network at higher concentrations. The transition between these régimes is linked to the changing local and intermediate-scale structure in the melts. The decoupling phenomenon is associated with the appearance of migration channels in the network which leads to cooperative effects in the Li+ migration.